1997
DOI: 10.1080/713613166
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of children and community members concerning the circumstances of orphans in rural Zimbabwe

Abstract: Focus group discussions and interviews were held with 40 orphans, 25 caretakers and 33 other community workers from a rural area near Mutare, Zimbabwe. Orphan concerns included feeling different from other children, stress, stigmatization, exploitation, schooling, lack of visits and neglect of support responsibilities by relatives. Many community members, while recognizing their limitations due to poverty, were already actively helping orphans and caretakers. Extended family networks are the primary resource f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 2 publications
3
88
1
2
Order By: Relevance
“…Kamali et al [19] found that orphans generally seemed taken good care of by the community, which is in line with other studies [13,20] that find the orphans satisfactorily looked after as their basic needs are met by their extended family, even though it sometimes is in extreme deprivation [21]. Oleke et al [21] have pointed out that the view on how orphans are catered for during the AIDS epidemic might be somewhat optimistic and Baylies [22] describes the extended family as "safety net with holes", as the protection and care offered depends on an individual's status in the network.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Kamali et al [19] found that orphans generally seemed taken good care of by the community, which is in line with other studies [13,20] that find the orphans satisfactorily looked after as their basic needs are met by their extended family, even though it sometimes is in extreme deprivation [21]. Oleke et al [21] have pointed out that the view on how orphans are catered for during the AIDS epidemic might be somewhat optimistic and Baylies [22] describes the extended family as "safety net with holes", as the protection and care offered depends on an individual's status in the network.…”
Section: Introductionsupporting
confidence: 81%
“…In this family the boy gets his basic physical needs fulfilled, which was not the case, when the father was alive and the family had to starve. According to Kamali et al [19] and Foster [13,20] his actual situation could be described as satisfactorily taken care of, and better as when he was staying with his father. We do not know, however, whether his psychological needs are met or whether the fact that he is staying with maternal kin provides an insecure future as pointed out by Oleke et al [23] and which psychological consequences this might have.…”
Section: Family Form and Stabilitymentioning
confidence: 99%
“…Although few published studies have examined the psychological well-being of children orphaned by AIDS in resource-poor countries, data from Africa suggest that AIDS orphans reported a higher level of depression than children orphaned by other causes or children in intact families (Atwine et al, 2005;Foster, 1997;Sengendo & Nambi, 1997). In addition to the obstacles faced by children orphaned by other causes, characteristics unique to AIDS may create additional cognitive and social barriers for grief resolution among AIDS orphans and place these children at an especially heightened risk for behavioral and emotional problems Sachs & Sachs, 2004;Zhao et al, in press).…”
Section: Effect Of Aids On Bereaved Children In Developing Countries:mentioning
confidence: 99%
“…First, a considerable number of orphaned children were placed in the care of the elderly in the extended family (Foster, 1997;Notzi, 1997). Elderly people face multiple challenges that include limited income, struggling to cope with the loss of loved ones, and poor adjustment to the role change from being provided for to being the provider (Hunter, 1990).…”
Section: Lack Of Adequate Carementioning
confidence: 99%
“…Bereaved children experienced multiple stressors that complicated their grief process. Literature reveals that children experience anger, guilt, yearning, denial, shock, disbelief, depression (Ribbens McCarthy 2006), low cognition (Gwandure, 2007); anxiety, irritability (Makaya, Mboussou, Bansimba, Ndinga, Ambendet & Puruehnce, 2002); lowered self-esteem and motivation (Rembe, 2006); sadness, pain, fear (Foster, Makufa, Drew, Mashumba & Kambeu, 1997); suicidal ideation, aggression and posttraumatic stress disorder (de Witt & Lessing 2005;Ndetei et al, 2008;Yule 2001). Parental death is viewed as very depressive.…”
Section: Psychological Consequencesmentioning
confidence: 99%